Mechanisms of disease: pathophysiological concepts of stroke in hemodynamic risk zones : do hypoperfusion and embolism interact? - Förster, Alex; Szabo, Kristina; Hennerici, Michael G. (Nature Clinical Practice. Neurology, 2008)
Over the past century, the pathophysiology of ischemia in the borderzones between the large cerebral arteries has been the topic of considerable debate. Two seemingly mutually exclusive mechanisms—hemodynamic failure and microembolism—have been proposed to explain this phenomenon. As Förster et al. discuss in this article, a new model of borderzone infarction, incorporating both hypoperfusion and microembolism, is now emerging.
Gesehen am 24.03.2021